Peningkatan Spiritual Masyarakat Dusun Piyaman II Melalui Kajian Intensif Program Kukerta - Wirayoga, Habil Achmad; Nurrahmat, Muhammad Arif; Hermawan, Hermawan (Efada : Jurnal Pengabdian Masyarakat, 2024)
Piyaman II Hamlet located in the village of Piyaman, Wonosari District, Gunungkidul Regency, has a religious background that can be categorized as quite good. With religious guidance from the Muhammadiyah organization, religious study sessions are often held in mosques and residents' homes, especially in Piyaman II Hamlet. Additionally, a grand religious study session is regularly conducted every 30-35 days in Piyaman Village, attended by nearly 1000 worshipers each time. Considering this background, we, as Kukerta students with a religious education background, have a program for nurturing and enhancing the spiritual well-being of the residents of Piyaman II Hamlet through post-congregational prayer lectures (kultum), weekly studies at various locations, and grand religious study sessions led by 2 field supervisors. The implementation of this program has received positive and very good responses because the residents of Piyaman II Hamlet are familiar with and accustomed to these religious study sessions. Another feedback from the residents is that the post-congregational prayer lectures and weekly studies conducted by students help increase their knowledge about religion and remind them of previously heard teachings. Furthermore, the grand religious study sessions led by field supervisors are attended by nearly 100 worshipers from Piyaman II Hamlet and surrounding hamlets.